Pancasila as a Nation and State Guideline: The Future Challenges - Fatmawati, Nuria (Jurnal Scientia Indonesia, 2018)
Pancasila as the source of all legal sources has gained legitimacy by juridical through the MPR TAP Number XX / MPRS / 1966 concerning the DPR-GR Memorandum Concerning the Source of Legal Order of the Republic of Indonesia and the Order of Legislation of the Republic of Indonesia. After reformation, entering the Pancasila was reaffirmed in Law Number 10 of 2004 which was later replaced by Law Number 12 of 2011 concerning Legislation. Pancasila as a source of all legal sources gives the meaning of the mandatory national legal system based on Pancasila. However, the need for Pancasila is increasingly eroded in the national legal system. This is motivated by three reasons, namely: first, there is an opposing attitude towards the New Order that uses Pancasila for the perpetuation of authoritarian authority. Second, strengthen legal pluralism that replaces contradictions or legal disharmony. Third, the status of the Pancasila is only a symbol of the law. For this reason, efforts need to be made to implement Pancasila as the source of all legal sources in the national legal system, namely: first, making Pancasila a source of law so that legal disharmony is not repeated when legal pluralism is used. Second, put Pancasila as the pinnacle of legislation so that Pancasila has a binding force on all types of legislation so that it does not oppose the principle of lex superiori derogat legi inferiori.